A history of contemporary Chinese literature - Hong, Zicheng (Brill's humanities in China library ;, 2007)
"A thorough overview and analysis of the literary scene in China during the 1949-1999 period, focusing primarily on fiction, poetry, drama, and prose writing"--Provided by publisher.